HUBUNGAN TINGKAT PENGETAHUAN PASIEN HIPERTENSI DENGAN UPAYA PENGENDALIAN HIPERTENSI DI UPTD PUSKESMAS PEMBANTU BERNGAM BINJAI - Leli Herawati (Universitas Prima Indonesia, 2020)
WHO (World Health Organization) noted that in 2013 at least 839 million cases of hypertension occurred worldwide. In Indonesia there was an increase in the prevalence of hypertension. Overall the prevalence of hypertension in Indonesia in 2013 was 26.5% 1. And in North Sumatra, the prevalence of hypertension in 2013 was 24.7%. People with hypertension are increasing every year almost all over the world and cause global public health problems that contribute to the burden of heart disease, stroke, kidney failure, disability and premature death. This type of research is an analytical quantitative study with cross-sectional design, with a total sample of 56 people with hypertension and the sampling technique used is simple random sampling. Data analysis using chi square test. The results of the study were 45-54 years old (35.7%), female gender (53.6%), high school education (42.9%) and the work of farmers / fishermen / laborers 37.5%). Good level of knowledge (67.9%), adequate hypertension control efforts (64.3%) Chi square test results showed variables related to hypertension control efforts were education, occupation, knowledge of hypertensive patients (p <0.05). It is recommended for the puskesmas to improve health implementation programs, especially early detection of hypertension so that prevention programs can be done quickly to avoid more severe hypertension. It is hoped that the community will participate in the Healthy Living Movement (GERMAS) program, which focuses on three activities, namely: doing 30 minutes of exercise a day, eating fruits and vegetables; and check health regularly.